2015
DOI: 10.1016/j.aquatox.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive biomonitoring suggest metabolic adaptation in blue mussels ( Mytilus spp.) chronically exposed to a moderate contamination in Brest harbor (France)

Abstract: Brest harbor (Bay of Brest, Brittany, France) has a severe past of anthropogenic chemical contamination, but inputs tended to decrease, indicating a reassessment of its ecotoxicological status should be carried out. Here, native and caged mussels (Mytilus spp.) were used in combination to evaluate biological effects of chronic chemical contamination in Brest harbor. Polycyclic aromatic hydrocarbon (PAH) contamination was measured in mussel tissues as a proxy of harbor and urban pollution. Biochemical biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 71 publications
2
29
0
1
Order By: Relevance
“…The river provides more than 63% of the bay's freshwater supply (Auffret, 1983). Lacroix et al (2015) observed differences in physiological responses to contaminants between native Brest Bay and imported mussels. Non-natives were more sensitive and showed more sensitive biomarker responses.…”
Section: Chemical Contaminationmentioning
confidence: 85%
“…The river provides more than 63% of the bay's freshwater supply (Auffret, 1983). Lacroix et al (2015) observed differences in physiological responses to contaminants between native Brest Bay and imported mussels. Non-natives were more sensitive and showed more sensitive biomarker responses.…”
Section: Chemical Contaminationmentioning
confidence: 85%
“…Mussels (58.6 ± 9.6 mm, mean ± SD) were collected at the Pointe d'Armorique in the Bay of Brest (48 19'20.29 00 N, Brittany, France), a site known to exhibit low PAH concentrations (Lacroix et al, 2015). The sampling site is located within a zone of overlap between Mytilus edulis and Mytilus galloprovincialis (Bierne et al, 2003), the mussel population is thus considered as a "species complex" (Lacroix et al, 2014a), and is referred to as Mytilus spp.…”
Section: Mussel Collection and Acclimatizationmentioning
confidence: 99%
“…The evaluation of the impact of pollutants in the environment is now a major concern, with the aim of reaching a good chemical and ecological state of the littoral zone. Previous studies (Milinkovitch et al, 2015;Lacroix et al, 2015;Luna-Acosta et al, 2011;Breitwieser et al, 2016) showed the risks of chronic chemical contamination and the consequences in the bivalves Mimachlamys varia, Crassostrea gigas and Mytilus edulis in an open coastal environment. In this context, the objective of this project was to assess the impacts of pollution (heavy metals) on the macrofauna of a semi-closed environment: a marina in La Rochelle (France).…”
Section: Introductionmentioning
confidence: 99%